Lactobacillus crispatus S-layer proteins modulate innate immune response and inflammation in the lower female reproductive tract - Alexiane Decout; Ioannis Krasias; Lauren Roberts; Belen Gimeno Molina; Chloé Charenton; Daniel Brown Romero; Qiong Y. Tee; Julian R. Marchesi; Sherrianne Ng; Lynne Sykes; Phillip R. Bennett; David A. MacIntyre (Nature Communications)
Abstract Lactobacillus species dominance of the vaginal microbiome is a hallmark of vaginal health. Pathogen displacement of vaginal lactobacilli drives innate immune activation and mucosal barrier disruption, increasing the risks of STI acquisition and, in pregnancy, of preterm birth. We describe differential TLR mediated activation of the proinflammatory transcription factor NF-κB by vaginal pathogens and commensals. Vaginal Lactobacillus strains associated with optimal health selectively interact with anti-inflammatory innate immune receptors whereas species associated with suboptimal health including L. iners and Gardnerella vaginalis interact with both pro- and anti-inflammatory receptors. Anti-inflammatory action of L. crispatus is regulated by surface layer protein (SLPs)-mediated shielding of TLR ligands and selective interaction with the anti-inflammatory receptor DC-SIGN. Detection of SLPs within cervicovaginal fluid samples is associated with decreased concentrations of pro-inflammatory cytokines in Lactobacillus crispatus-dominated samples. These data offer mechanistic insights into how vaginal microbiota modulate host immune response and thus reproductive health and disease states.